FROM SUBSISTENCE TO FINANCIAL ASSET: THE APPROPRIATION OF THE BRAZILIAN CERRADO LANDS AS A RESOURCE/ De subsistência à ativo financeiro: a apropriação como recurso das terras do Cerrado brasileiro/ la subsistencia a los activos financieros: apropiación como recurso de tierras del Cerrado brasileño - Frederico, Samuel (REVISTA NERA, 2019)
This article proposes a typology of the appropriation of Brazilian Cerrado lands as a resource—ranging from subsistence for local peoples, to the current attempt by institutional investors to transform the land into a financial asset—without disregarding its use as a source of power and accumulation by large capitalist farmers. A resource is considered as any product of a relationship mediated by appropriation of a specific natural material by a particular agent. Until 1970s, Cerrado lands were used almost exclusively as a means of subsistence by peasants and indigenous populations. Since then, under a violent expropriation process, land has become a resource for capitalist accumulation and patrimonialist power for large-scale immigrant farmers, with the expansion of the agricultural frontier. Within the context of land grabbing in the 21st century, the arrival of representatives of international financial capital has added to the complexity of the appropriation strategies in which Cerrado lands are considered financial assets. These different perspectives of using land as a resource has increased the number of conflicts and contradictions, with profound negative effects on peasant communities in agricultural frontier areas.